Conversion of Plexiform Neurofibroma to a Malignant Peripheral Nerve Sheath Tumour: A Case Report in a Patient with Neurofibromatosis-1 - Tebogo Linky Medupe (Achievements and Challenges of Medicine and Medical Science Vol. 7, 2024)
Neurofibromatosis type-1 is a frequently occurring syndrome predisposing to tumors, with an estimated prevalence of 1 in 3000 individuals. It is a multisystem illness that exhibits a broad spectrum of clinical symptoms along with elevated morbidity and mortality. One of the most prevalent dominantly inherited genetic disorders is neurofibromatosis-1. The majority of epidemiological research has indicated that at least one in three thousand people experience this globally. Neurofibromatosis-1 people are more likely to develop cancer, and the illness affects several systems, with primary manifestations occurring in the cutaneous, neurologic, and orthopaedic sites. These conditions can cause severe morbidity or fatality. The neurocutaneous-skeletal neurofibromatosis1 (NF1) syndrome can only be caused by a mutation in the NF1 gene; nevertheless, the pathogenesis of the disease’s various manifestations in various organ systems appears to be becoming more intricate. The formation, severity, and prognosis of a wide range of distinct clinical phenotypes appear to be caused by interactions between many cell types, cell signaling networks, and the extracellular matrix. A "second hit" that causes the NF1 gene to become bi-allelic inactivated appears to be critical for the development of several symptoms, including neurofibromas, café-au-lait macules, and glomus tumors. We present a rare example of a plexiform neurofibroma undergoing malignant transformation from our database of cases. In order to increase public knowledge of the condition and genetic testing, a review of the disease is required. Moreover, incomplete surgery can be reduced with local extension and involvement of the surrounding structures. It is imperative to time the procedure perfectly. Although NF-1-related lesions will inevitably develop, early lesion treatments and genetic testing may increase the likelihood of survival.